2017
DOI: 10.3892/or.2017.5762
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of microRNA-320b correlates with tumorigenesis and unfavorable prognosis in glioma

Abstract: Accumulating evidence demonstrates that dysregulated microRNAs (miRNAs) play a critical role in tumorigenesis and progression of various cancers. miR-320b, a member of miR‑320 family, was revealed downregulated in numerous human cancers, including nasopharyngeal carcinoma and colorectal cancer. However, the function of miR‑320b in human glioma remained poorly defined. In this study, we report that miR‑320b was lowly expressed in glioma tissues and cell lines in contrast with controls, being closely correlated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…Substantial evidence indicates that miRNAs play important roles in most biological processes in both normal development and in various diseases, including cancer (12,13). In recent years, miRNA dysregulation has been reported in various types of human cancers, such as GC (14), bladder cancer (15), colorectal cancer (16), glioma (17) and lung cancer (18). Furthermore, aberrantly expressed miRNAs are associated with tumourigenesis and tumour development and affect cell proliferation, cell cycle distribution, apoptosis, migration, invasion, angiogenesis and epithelial-mesenchymal transition (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Substantial evidence indicates that miRNAs play important roles in most biological processes in both normal development and in various diseases, including cancer (12,13). In recent years, miRNA dysregulation has been reported in various types of human cancers, such as GC (14), bladder cancer (15), colorectal cancer (16), glioma (17) and lung cancer (18). Furthermore, aberrantly expressed miRNAs are associated with tumourigenesis and tumour development and affect cell proliferation, cell cycle distribution, apoptosis, migration, invasion, angiogenesis and epithelial-mesenchymal transition (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…miRNA-320b is down-regulated in various cancers, and it is associated with tumorigenesis and poor prognosis in glioma. 42 miRNA-375 was also shown to be often down-regulated in NSCLC, 43,44 breast cancer, 45 colorectal cancer, [46][47][48][49] oesophageal cancer, 50,51 gastric cancer, 52,53 and pancreatic cancer. 54,55 It is associated with tumour proliferation and metastases.…”
Section: Discussionmentioning
confidence: 99%
“…microRNAs (miRs or miRNAs) are a class of endogenous non-coding small RNAs, 18-24 nucleotides in length, that are ubiquitous in viruses and eukaryote cells in highly conserved sequences. It has been estimated that up to 50% of human protein-coding genes are regulated by miRNAs (4). Each miRNA has the potential to regulate hundreds of RNAs, and their expression is associated with tissue status and disease subtype (5).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs have been demonstrated to serve an important role in the development and prognosis of glioma. Lv et al (4) reported that low miR-320b expression in glioma was associated with poor patient prognosis. The upregulation of miR-320b enhanced apoptosis and attenuated the proliferation, migration and invasive abilities of glioma cells.…”
Section: Introductionmentioning
confidence: 99%